The Effectiveness of the Snakes and Ladders Game as a Learning Medium to Enhance Mathematics Learning Motivation Among Seventh-Grade Students - Rizka Fadila; Laili Habibah; Sakinah Ubudiyah Siregar (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2026)
Math can seem really hard to middle schoolers, and because of that it can be a less motivating subject for them. As teachers we need to make school more fun and more stimulating. One way I looked at doing that is with the Snakes and Ladders game. My goal was to see how much this game would motivate 7th graders to learn more about Integer Algebra. My study incorporated 25 different students, and the data I used came from a motivation to learn survey I created. I made sure everything from the survey was validated, and elements like consistency and difficulty assessment were created. Based on the results of my study, the Snakes and Ladders game motivated the students to get more involved in the more fun and energetic classroom. The Snakes and Ladders game for motivated the students. I would recommend this game to other teachers because it helps engage students. For motivating younger students to learn math, I would call this a success. My only other recommendation is to use more detailed statistics to justify the success of using Snakes and Ladders as a learning resource on a larger population.